Proximate Characteristics and Antioxidant Activity of Polyherbal Extract in Yogurt - Meta Andhini Noor Chandra; Epi Taufik; Kintoko Kintoko (Institut Pertanian Bogor, 2025)
Fermented dairy products, such as yogurt, are well known for their health advantages. Enhancing their functional value using polyherbal mixtures constitutes a big step forward in functional food development. This study looks at the proximate composition (fat, protein, moisture, and ash content) and antioxidant activity of polyherbal yogurt enriched with green tea, cinnamon, and fenugreek seed extracts. Formulations were created with varied amounts of polyherbal extract at 0% (P0), 1% (P1), 2% (P2), and 3% (P3), with Lactobacillus bulgaricus and Streptococcus thermophilus as starter cultures (Lactina Ltd). A completely randomized design with three replications was used, and the data were analyzed using ANOVA at a 95% confidence level. The results showed substantial variations in fat (2.84−3.62%) and moisture (88.17−8.83%) content between treatments. Protein (3.92−5.03%) and ash level (0.76−0.77%) met the Indonesian National Standard (SNI) for yogurt. Polyherbal yogurt demonstrated considerably higher antioxidant activity and capacity than the control. The control yogurt (P0) had a poor antioxidant capacity of 60.81±10.89%, while polyherbal yogurt (P1, P2, and P3) had a high antioxidant capacity ranging from 252.40±11.20% to 267.44±1.44%. These findings indicate that including polyherbal extracts into yogurt not only ensures compliance with national nutritional standards (SNI), but also considerably increases antioxidant potential. Thus, polyherbal yogurt is an appealing prospect for development as a beneficial dairy product. Keywords: antioxidant, polyherbal, proximate, yogurt